Unveiling the Critical Role of REX1 in the Regulation of Human Stem Cell Pluripotency. (November 2013) - Son, Mi‐Young; Choi, Hoonsung; Han, Yong‐Mahn; Sook Cho, Yee
Abstract Reduced expression 1 (REX1) is a widely used pluripotency marker, but little is known about its roles in pluripotency. Here, we show that REX1 is functionally important in the reacquisition and maintenance of pluripotency. REX1‐depleted human pluripotent stem cells (hPSCs) lose their self‐renewal capacity and full differentiation potential, especially their mesoderm lineage potential. Cyclin B1/B2 expression was found to parallel that of REX1. REX1 positively regulates the transcriptional activity of cyclin B1/B2 through binding to their promoters. REX1 induces the phosphorylation of DRP1 at Ser616 by cyclin B/CDK1, which leads to mitochondrial fission and appears to be important for meeting the high‐energy demands of highly glycolytic hPSCs. During reprogramming to pluripotency by defined factors (OCT4, SOX2, KLF4, and c‐MYC), the reprogramming kinetics and efficiency are markedly improved by adding REX1 or replacing KLF4 with REX1. These improvements are achieved by lowering reprogramming barriers (growth arrest and apoptosis), by enhancing mitochondrial fission, and by conversion to glycolytic metabolism, dependent on the cyclin B1/B2‐DRP1 pathway. Our results show that a novel pluripotency regulator, REX1, is essential for pluripotency and reprogramming. Stem Cells2013;31:2374–2387